A new oral testosterone (TLANDO) treatment regimen without dose titration requirement for male hypogonadism. (18th January 2022) - DelConte, Anthony; Papangkorn, Kongnara; Kim, Kilyoung; Bruno, Benjamin J.; Chidambaram, Nachiappan; Khera, Mohit; Goldstein, Irwin; Kohler, Tobias S.; Miner, Martin; Dobs, Adrian S.; Patel, Mahesh V.
Abstract: Background: Male hypogonadism (testosterone level < 300 ng/dl) is a clinical syndrome that results from failure of the testis to produce physiological levels of testosterone. Most marketed testosterone replacement therapy products often require multiple dose adjustment clinic visits to achieve the desired, eugonadal testosterone levels. Objective: To evaluate the efficacy and safety of a novel oral testosterone undecanoate therapy for the treatment of hypogonadism. Material and methods: Ninety‐five ( N = 95) hypogonadal men were enrolled in this open‐label, single‐arm, multicenter study in the United States (NCT03242590). Subjects received 225 mg of oral testosterone undecanoate (TLANDO) twice a day for 24 days without dose adjustment. Primary efficacy was percentages of subjects who achieved mean 24‐h testosterone levels within the eugonadal range and secondary efficacies were evaluated based on the upper limit of lab normal range of testosterone concentration. Results: Subjects enrolled were on average age of 56 years, with about 17% of subjects older than 65 years. The mean body mass index was 32.8 kg/m 2 . The baseline mean total testosterone values were below the normal range (202 ± 74 ng/dl). Post‐treatment with 450 mg testosterone undecanoate daily dose without dose adjustment, 80% of subjects (95% confidence interval of 72%–88%) achieved a testosterone Cavg in the normal range and restored testosterone levels to mean testosterone Cavg of 476 ± 184 ng/dl at steady state. Testosterone restoration was comparable to other approved testosterone replacement therapy products. TLANDO was well tolerated with no deaths, no drug‐related serious adverse events, and no hepatic adverse events. Discussion and conclusions: TLANDO restored testosterone levels to the normal range in the majority of hypogonadal males. This new oral testosterone replacement therapy can provide an option for no‐titration oral testosterone replacement therapy. This therapy has the potential to improve patient compliance in testosterone replacement therapy.